2009
DOI: 10.1513/pats.200905-029ds
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Computed Tomography Measurements of Peripheral Lung Pathology in Chronic Obstructive Pulmonary Disease

Abstract: Background: The smaller airways, , 2 mm in diameter, offer little resistance in normal lungs, but become the major site of obstruction in chronic obstructive pulmonary disease (COPD). Objective: To examine bronchiolar remodeling and alveolar destruction in COPD using micro-computed tomography (micro-CT). Methods: Micro-CT was used to measure the number and crosssectional lumen area of terminal bronchioles (TB) and alveolar mean linear intercept (Lm) in 4 lungs removed from patients with very severe (GOLD-4) CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 26 publications
(19 reference statements)
2
42
0
Order By: Relevance
“…It has the advantage over HRCT to achieve a better resolution, allowing for direct images of both bronchiolar and alveolar structures [91]. However, with current technology, use of micro-CT is limited to ex vivo tissue samples because the level of radiation associated with micro-CT damages tissue [92]. HOGG et al [92] used micro-CT to evaluate morphological changes in human lungs obtained during transplantation in subjects with severe COPD and in unused donor lungs that served as controls.…”
Section: Integrative Medicine For Small Airways Disease In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the advantage over HRCT to achieve a better resolution, allowing for direct images of both bronchiolar and alveolar structures [91]. However, with current technology, use of micro-CT is limited to ex vivo tissue samples because the level of radiation associated with micro-CT damages tissue [92]. HOGG et al [92] used micro-CT to evaluate morphological changes in human lungs obtained during transplantation in subjects with severe COPD and in unused donor lungs that served as controls.…”
Section: Integrative Medicine For Small Airways Disease In Copdmentioning
confidence: 99%
“…However, with current technology, use of micro-CT is limited to ex vivo tissue samples because the level of radiation associated with micro-CT damages tissue [92]. HOGG et al [92] used micro-CT to evaluate morphological changes in human lungs obtained during transplantation in subjects with severe COPD and in unused donor lungs that served as controls. The entire lungs were inflated near TLC and frozen with liquid nitrogen.…”
Section: Integrative Medicine For Small Airways Disease In Copdmentioning
confidence: 99%
“…Quantitative micro-CT studies of human lung pathologies focus most often on airway alterations in emphysema. 2 D measurements like mean linear intercept, and the quantification of terminal bronchioles in number and diameter provide insight into the rarefaction of small airways and the different temporal onset of narrowing and collapse of terminal bronchioles versus the emphysematous destruction of alveolar tissue [18,19]. Nevertheless, it does not quantify the loss of tissue.…”
Section: Figmentioning
confidence: 99%
“…Importantly, BLACK et al [53] have recently reported a similar loss of elastic fibres in small conducting airways of COPD subjects, suggesting that small conducting airways may also disappear. A major question resulting from these findings relates to the number of small conducting airways in COPD subjects [54,55]. HOGG et al [55] have reported preliminary data using micro-computed tomography (CT) in isolated lungs and suggested a reduction in the number of small conducting airways in subjects with centrilobular emphysema.…”
Section: Alveolimentioning
confidence: 99%
“…A major question resulting from these findings relates to the number of small conducting airways in COPD subjects [54,55]. HOGG et al [55] have reported preliminary data using micro-computed tomography (CT) in isolated lungs and suggested a reduction in the number of small conducting airways in subjects with centrilobular emphysema. Decreased numbers of small conducting airways may contribute to increased resistance in small airways because mathematical computation indicates that a 50% reduction in the number of small conducting airways will result in a two-fold increase in resistance.…”
Section: Alveolimentioning
confidence: 99%